DIAGNOSTIC SYSTEM FOR OPTIMIZING THE DIESEL LOCOMOTIVE COOLING MODES - V.P. Perevertov; N.K. Yurkov; N.V. Chertykovtseva; V.N. Novikova; N.A. Kuzin (Надежность и качество сложных систем)
Background. The paper presents a diagnostic system for optimizing the operating modes of the diesel locomotive cooling system, the components of which are: a diagnostic algorithm and hardware selection for import substitution, a structural and functional diagram (model). Materials and methods. The system is adapted to changes in outside air temperature by using methods for identifying thermal parameters in the cooling-warming modes of diesel locomotive power plants; it is implemented on the basis of the ldm-sam7x128 controller-designer. The software is written in C++ with partial use of the assembler language. Results and conclusions. The proposed algorithm and diagnostic methods make it possible to increase the reliability of power equipment in the substation of the Russian Railways highspeed transport system. A diagnostic system equipped with an intelligent sensor automates this process by reading its parameters via a digital channel from the EPD chip. The TEDS specification allows for automatic configuration of the sensor and simplifies its alignment with other electronic equipment. All information about the sensor is stored in theTEDS memory of the integrated circuit, eliminating the need to create a separate database for storing calibration information.